Effect of applying no-touch technique for venous dissection on the maturation of autogenous arteriovenous fistula - Chao-jin Chen; Zi-zhao Jiao; Chun-hua Zhang (Editorial Department of Journal of Clinical Nephrology, 2024)
Injuries of vein and its vasa vasorum caused by venous dissection may create autologous arteriovenous fistula（AVF） in patients on maintenance hemodialysis （MHD）. Affecting the proliferation, migration, phenotypic transformation of vascular cells and extracellular matrix（ECM） remodeling of vascular wall, inflammatory reaction, hypoxia of dissected vein, negative vascular remodeling and maturation obstacle of AVF played some important roles in the occurrence of AVF maturation obstacle. As proposed by Souza et al, no-touch technique（NTT） for venous dissection was initially utilized for harvesting great saphenous vein during coronary artery bypass grafting. As compared with conventional techniques（CT） for venous dissection, NTT could alleviate the injuries of vein and its vasa vasorum and boost the postoperative patency rate of venous grafts. In recent years, NTT has also been applied for venous dissection in creating AVF in MHD patients. Thus it offers a novel surgical approach for promoting AVF maturation and lowering the incidence of AVF maturation obstacle. This review focused upon the mechanism of NTT promoting AVF maturation and lowering the incidence of maturation obstacle of AVF.